Identifying and evaluating the challenges facing the management of digital libraries - Rahmani, Mehdi (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2022)
Background and purpose: With the advancement of science and the increase of electronic resources, the need to create libraries to collect, organize and disseminate these types of resources is felt. With the growth of electronic resources, resource management has gained special importance and is one of the important areas and issues in the discussion of digital libraries. In this study, the aim is to examine the issues and challenges facing the management of digital libraries and provide solutions to solve the challenges and issues facing digital libraries and digital library management. Research method: The current research is applied in terms of purpose and survey research in terms of method. The current research has been conducted by field method and using library techniques, and the researchers have presented digital library management approaches by reviewing the published texts on digital libraries and digital library management issues. Findings: The results of the research showed that the most important components of digital library management include human resources, management of shared resources, author’s right to update resources, cataloging and maintaining the technical structure. Also, the surveys showed that the most important challenge facing digital libraries is the issue of intellectual property and compliance with copyright laws. Conclusion: The results of the research showed that in digital libraries, as in traditional libraries, measures must be taken in the field of collecting, organizing, storing and disseminating information, and it is not possible to carry out the above-mentioned activities without a competent manager. Digital library management leads to the creation of coordination between different parts of the digital library and helps the library to achieve the desired goals. The digital library is facing many issues and challenges, including financial and budget issues, issues related to expert human resources, issues related to digital equipment and internet infrastructure, issues related to author’s right and copyright, issues related to the lack of devices. Digitization and security of important information resources and documents and finally issues related to the protection and maintenance of digital resources are faced, which cannot be solved except with the presence of a capable manager and strong human resources of the library.